2002
DOI: 10.1159/000057341
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Photoinhibition on the Morphology and Function of Pituitary Lactotropes in Male Golden Hamsters

Abstract: Inhibition of prolactin (PRL) secretion has been previously shown in pituitaries from male and female hamsters exposed to short photoperiods. The purpose of the present study was to analyze the possible quantitative immunohistochemical and ultrastructural changes of PRL cells in male golden hamsters undergoing regression and spontaneous recrudescence, correlating the morphological findings with circulating PRL levels. Thus, adult male golden hamsters were exposed for 8, 16, 22 and 28 weeks to either short phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Morphometric studies were performed as previously reported in detail. 24 Briefly, measurements of adipocyte parameters were made with an image analysis system (Imaging Technology, Optimas 5.2). Each field of immunostained cells in the reference area (RA; area scanned where adipocytes were scored) was measured for an average of 10 micrographs taken from two levels (e.g.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Morphometric studies were performed as previously reported in detail. 24 Briefly, measurements of adipocyte parameters were made with an image analysis system (Imaging Technology, Optimas 5.2). Each field of immunostained cells in the reference area (RA; area scanned where adipocytes were scored) was measured for an average of 10 micrographs taken from two levels (e.g.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Morphometry was performed as reported in detail previously [Cónsole et al, 2002]. Stated in brief, immunostained pituitary cells were assessed by means of an image analysis system (Imaging Technology, Optimas 5.2).…”
Section: Morphometrymentioning
confidence: 99%
“…Morphometry was performed as reported in detail previously [21]. Measurements of immunostained lactotrope cells were made by means of an image-analysis system (Imaging Technology, Optimas 5.2).…”
Section: Methodsmentioning
confidence: 99%